Needs Analysis of Tourism Destination Study Program as a New Study Program at Politeknik Negeri Jember - Uystka Hikmatul Kamiliyah NH; Alfi Hidayatu Miqawati (Journal of Language, Communication, and Tourism, 2023)
Being a newly established study program, the Tourism Destination Study Program of Politeknik Negeri Jember had several needs to be completed to support the teaching and learning process. This study aimed to determine the needs of the Tourism Destination Study Program to support its teaching-learning process. This study deployed a descriptive qualitative method. The informants of this study were lecturers and students in the Tourism Destination Study Program of Politeknik Negeri Jember. The data were obtained from field observations in the Tourism Destination Study Program, interviews with lecturers and students, and field documentation. The results showed that there were three things needed by the tourism destination study program, including (1) a tourism laboratory or studio in the Tourism Destination Study Program, (2) an integrated field practicum instrument for Tourism Destination Study Program students and, (3) teaching materials to open students' perspectives on service management in the Tourism Destination Study Program of Politeknik Negeri Jember.